Epidemiology of Poisoning Cases at Lumbini Medical College, Nepal: A 5‐Year Retrospective Study - Samata Nepal; Alok Atreya; Prakriti Regmi; Prasun Shrestha; Rishav Babu Shrestha; Laxmi Prasad Sapkota; Ritesh G. Menezes; Himal Ghimire; Suraj Dhakal; Shikha Pahari (Health Science Reports)
ABSTRACT Background and Aims Poisoning is a major global public health problem, disproportionately burdensome in low‐resource healthcare settings. The objective of this study was to gain epidemiological insights into poisoning cases at Lumbini Medical College and Teaching Hospital over a period of 5 years. Methods A retrospective cross‐sectional analysis was performed of hospital records and 402 poisoning cases admitted to Lumbini Medical College between January 2019 and May 2024 were analyzed descriptively using SPSS V.27.0. The study meticulously documented a wide range of data, such as patient demographics, types of poisons, contexts for poisoning, clinical presentation, and medical outcomes. Results Of 402 cases, females predominated (61.2%, n = 246), with a median age of 26.5 years (IQR: 18.2–39.2). Pesticides, particularly organophosphates, were the leading agent (57.7%, n = 232), with self‐harm as the primary reason (70.9%, n = 285), often linked to family conflict. Poisoning peaked in the evening, notably among females aged 25–44 years (42.3%, n = 170). Mortality was low (0.2%, n = 1), with 68.7% of patients receiving some form of psychiatric consultation. Conclusions Poisoning primarily involved young, married females using organophosphorus pesticides for self‐harm, often due to family conflict and mental health issues, with most receiving psychiatric consultation.